Isolation and Characterization of Thermophilic Bacteria as Cellulolytic Enzyme Producer from the Hot Spring of Ie Seuum Aceh Besar, Indonesia - RUHUL KHALILA; lenni fitri; SUHARTONO SUHARTONO (Indonesian Society for microbiology, 2020)
Cellulase enzymes can be isolated from thermophile bacteria obtained from the hot spring Ie Seuum, Aceh Besar. This research aimed to recover and characterize the isolates morphologically and biochemically followed by determination of the thermophile bacterial isolates potential as cellulolytic enzyme producers,. The sampling method in this research was conducted by a purposive sampling at temperature of 70 oC, 60 oC and 50 oC. Isolation of thermophilic bacteria was carried out on nutrient agar (NA) media. There were four isolates of thermophilic bacteria isolated recovered at 70 oC, five isolates at 60 oC, and seven isolates at 50 oC. Of the 18 isolates obtained, 15 of them were able to produce cellulase enzymes. Cellulase enzyme production can be determined by the presence of clear zones around bacterial colonies on CMC media after addition of 1% congo red drops and wash with 1 M NaCl. The highest five Cellulolytic Index (CI) values ​​were obtained from isolates ISB75; ISB64; ISB52; ISB54; ISB56 that were 1.23; 2.22; 1.39; 1.59; 1.10, respectively. Biochemical tests carried out on 5 isolates with the highest cellulolytic index values showed that the bacterial isolate were suspected to be from the genera of Bacillus sp.